2023
DOI: 10.21608/edj.2022.170734.2322
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of the framework material, veneering technique and aging on flexural strength of core/veneered restorations

Abstract: Objective: To evaluate the flexural strength of different combinations of modified PEEK and 3-YTZP veneered restorations as well as the effect of aging on those combinations. Materials and Methods:Two core materials; partially sintered tetragonal monolithic zirconia and modified PEEK, and three veneering materials; lithium disilicate glass-ceramic, packable composite, and veneering porcelain were used. A total of sixty specimens were randomly divided into 3 groups (n=20). The specimens were constructed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…All specimens in the present study were exposed to artificial aging in an attempt to simulate the oral conditions in agreement with previous studies which claim that thermal cycling did not affect the flexural strength or load-bearing capacity of PEEK [38]. However, other studies in the literature showed a significantly lower fracture resistance for the Crea.lign veneered PEEK cores after aging [34].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…All specimens in the present study were exposed to artificial aging in an attempt to simulate the oral conditions in agreement with previous studies which claim that thermal cycling did not affect the flexural strength or load-bearing capacity of PEEK [38]. However, other studies in the literature showed a significantly lower fracture resistance for the Crea.lign veneered PEEK cores after aging [34].…”
Section: Discussionsupporting
confidence: 87%
“…However, caution is advised when preparing 0.5-mm minimal thickness restorations [32,33]. Other studies showed that multiple factors are known to affect the entire strength of bi-layered restorations other than the thickness of the veneering material such as residual stress, interfacial bonding strength, the direction of loading, as well as the modulus of elasticity and fracture resistance of each layer [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation